The science of sound - Thomas D Rossing (Addison-Wesley, 1989)
The book explains a number of more advanced topics including the perception and measurement of sound, the human voice, and environmental noise. Lavishly illustrated with over 550 figures, the book provides all the basics for the notice, yet also supplies the in-depth, detailed information professionals need